2007
DOI: 10.1016/j.epsl.2006.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Extraterrestrial chromite in the resurge deposits of the early Late Ordovician Lockne crater, central Sweden

Abstract: The distribution of extraterrestrial chromite grains (N63 μm) has been studied in the resurge deposit of the early Late Ordovician (458 Ma) Lockne impact structure in central Sweden. A 1-kg-sample of resurge sediment from the rim of the crater is extremely rich in extraterrestrial chromite. In total the sample contains N 125 chromium spinel grains kg − 1 , most grains being chromite. Due to post-depositional alterations, the origin of several of the grains is dubious, although it is clear that the major part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 51 publications
3
47
1
Order By: Relevance
“…The TiO 2 concentration of the Gubbio EC grains is on average 0.4-0.7 wt% lower than in Ordovician EC grains. Previous studies have shown that the TiO 2 concentration of sediment-dispersed chromite grains in general is very resistant to weathering and diagenesis (Schmitz et al 2001;Schmitz and Häggström 2006;Alwmark and Schmitz 2007). Chromite in H chondrites is on average ~0.6-0.7 wt% lower in TiO 2 than in L chondrites (Bunch et al 1967;Schmitz et al 2001;Wlotzka 2005).…”
Section: And the Chemical Composition Is Shown Inmentioning
confidence: 94%
“…The TiO 2 concentration of the Gubbio EC grains is on average 0.4-0.7 wt% lower than in Ordovician EC grains. Previous studies have shown that the TiO 2 concentration of sediment-dispersed chromite grains in general is very resistant to weathering and diagenesis (Schmitz et al 2001;Schmitz and Häggström 2006;Alwmark and Schmitz 2007). Chromite in H chondrites is on average ~0.6-0.7 wt% lower in TiO 2 than in L chondrites (Bunch et al 1967;Schmitz et al 2001;Wlotzka 2005).…”
Section: And the Chemical Composition Is Shown Inmentioning
confidence: 94%
“…They show none of the features of altered grains from the Lockne impact crater resurge deposits, where hydrothermal activity has affected grains, or from a few of the fossil meteorites at Kinnekulle that show signs of severe corrosion Alwmark and Schmitz 2007). The TiO 2 content is one of the most stable features of the chromite chemistry during diagenesis.…”
Section: Brunflo Chromite Compositionmentioning
confidence: 99%
“…The replacement of Fe and sometimes Mg, with Zn, and in some cases also Mn, can dramatically alter the Fe content of a grain but does not have any significant effect on the Ti and Al contents. Another effect seen in some cases is a small increase, typically from 57 to 60-61 wt% in Cr 2 O 3 at the expense of FeO, which may cause a slight lowering of the TiO 2 concentration Alwmark and Schmitz 2007), but there is no indication of this in the Brunflo chromites. On the contrary, the Cr 2 O 3 concentrations of the Brunflo chromites are persistently low, on average 56.4 wt%, and FeO is high, on average 29.2 wt% (Tables 1-2).…”
Section: Brunflo Chromite Compositionmentioning
confidence: 99%
“…At 470 Ma the disruption of the L-chondrite parent body occurred (Anders, 1964;Korochantseva et al, 2007), and the high abundance of fossil meteoritic material in sediments from this time has been related to this event, based partly on the L-chondritic composition of relict chromite grains (Schmitz et al, 2001(Schmitz et al, , 2003Schmitz and Häggströ m, 2006). Because meteoritic material on the Earth surface is rapidly altered or weathered away, with the exception of chromite (FeCr 2 O 4 ), constituting 0.05-0.5 wt% of recent chondrites (Keil, 1962), the classification of the fossil chondritic material in these studies has been based mainly on elemental and O-isotopic composition of chromite (e.g., Schmitz et al, 2001;Alwmark and Schmitz, 2007;Greenwood et al, 2007). Both these 0016-7037/$ -see front matter Ó 2008 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…An analogue to the well established classification system for ordinary chondrites, founded on the fact that olivine and Ca-poor pyroxene in equilibrated (type 4-6) ordinary chondrites have specific ranges of chemical composition depending on group (H, L, LL; e.g., Mason, 1963;Keil and Fredriksson, 1964;Gomes and Keil, 1980;Rubin 1990), can then be established based on the inclusions. This would create an independent tool in the classification of fossil chondrites and sediment-dispersed extraterrestrial chromite grains originating from decomposed micrometeorites (Heck et al, 2008) and chondritic fragments related to impact events (Alwmark and Schmitz, 2007), when no matrix silicates are preserved or present.…”
Section: Introductionmentioning
confidence: 99%